Real optimization with SAP APO 30 tables - Kallrath, Josef; Maindl, Thomas I. (Springer, 2006)
This book describes and demonstrates how SAPÂ APO can be used to tackle real optimization problems arising in industry. In a unique combination it deals with the aspects of model-building as well as with the implementation in commercial supply chain management software, SAP APO being a typical example of an advanced planning system (APS).The authors address readers involved in optimization projects in which SAP and, particularly, SAP APO are implemented in companies. These are the project designers, projects leaders, the IT personnel inside....
Keywords: SAP APO